1989
DOI: 10.1007/bf00558064
|View full text |Cite
|
Sign up to set email alerts
|

Multiple publication of reports of drug trials

Abstract: Fourty-four multiple publications of 31 comparative trials of nonsteroidal anti-inflammatory drugs in rheumatoid arthritis were examined for mutual agreement. Thirty-two of the papers were published in the same language as the primary version. Important discrepancies were seen in 14 trials, involving description of the study design in two, exclusion of protocol violators in two, inconsistency in the number of effect variables in five, in the number of side-effects in five, and in the significance level in one.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 10 publications
1
58
0
Order By: Relevance
“…Duplicate publication is an identification issue, raised in the medical literature (Tramèr et al 1997;Gøtzsche 1989), that is currently unaddressed in the climate economics literature. Unlike the medical literature that discusses the potential bias from overt and covert re-publication of scientific results (e.g., with and without cross-references to original reports or data), we are concerned with potential bias from the common practices of updating climate-damage estimates over time and calibrating climate-model damage functions based on previous estimates in the climate damage literature.…”
Section: Conducting Meta-analyses Of Global Climate Damage Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicate publication is an identification issue, raised in the medical literature (Tramèr et al 1997;Gøtzsche 1989), that is currently unaddressed in the climate economics literature. Unlike the medical literature that discusses the potential bias from overt and covert re-publication of scientific results (e.g., with and without cross-references to original reports or data), we are concerned with potential bias from the common practices of updating climate-damage estimates over time and calibrating climate-model damage functions based on previous estimates in the climate damage literature.…”
Section: Conducting Meta-analyses Of Global Climate Damage Estimatesmentioning
confidence: 99%
“…Given that many of the estimates are updates or citations of previous estimates-giving a false sense of precision-we further limit our observations to prevent duplication bias (i.e., double counting) (Gøtzsche 1989;Tramèr et al 1997;Nelson and Kennedy 2009). We define a study as a duplicate if it is not the most up-to-date estimate by an author utilizing a particular method or if the estimate cites already-included estimates.…”
Section: Datamentioning
confidence: 99%
“…That supports earlier findings.4 Indeed, two trials with documented exclusions have published reports that indicate no exclusions. 25 Bias due to exclusions may exist in some of those trials that report no apparent exclusions, while many comparatively better trials may come from those in which authors reported exclusions. Some readers, however, may view trials without exclusions as less biased.…”
Section: Methodsmentioning
confidence: 99%
“…There was widespread discontent over selective publication of positive trial results and concealment of negative results, leading to distortion of the body of evidence available for clinical decision making [1][2][3]. As a result, there was a growing call for more transparency in the conduct and public disclosure of clinical trials [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…There was widespread discontent over selective publication of positive trial results and concealment of negative results, leading to distortion of the body of evidence available for clinical decision making [1][2][3]. As a result, there was a growing call for more transparency in the conduct and public disclosure of clinical trials [1][2][3]. Mandatory registration of all clinical trials, before trial commencement and recruitment of participants, was seen as a possible mechanism to ensure that all trial data would be available in the public domain, thus enabling clinicians, patients, researchers and health care planners to make informed choices [1][2][3].…”
Section: Introductionmentioning
confidence: 99%